Determining caregiver priorities for musculoskeletal interventions in children with Cerebral Palsy - Ragunandan, Shiksha (Division of General Surgery, 2026)
Introduction: Cerebral palsy is caused by an insult to the developing brain and typically results in the development of musculoskeletal deformity and resultant physical disability. These deformities are frequently addressed by non-invasive measures such as physiotherapy and splinting, but also by orthopaedic surgery. The musculoskeletal system is affected to varying degrees based on the severity of the cerebral insult and the goals of musculoskeletal interventions will vary accordingly. Little is known about what caregivers' expectations are following non-surgical or surgical interventions for musculoskeletal deformities and treatment is usually based on the expectations of the therapists or surgeons.. The aim of this study is to determine the treatment priorities of caregivers of children with cerebral palsy for musculoskeletal intervention. Methods: Participants were selected from the Red Cross Children's Hospital cerebral palsy clinic. They were divided into two groups of parents/guardians of children with cerebral palsy who were ambulatory and those who were non-ambulatory. There were 20 participants in each group who filled out a questionnaire regarding their expectations from interventions for their child. A Delphi consensus study design was used to prioritise responses given by participants in the questionnaire. There were two follow up iterative rounds to prioritise the list of responses given by asking participants to choose the top four responses relevant to them in the first iterative and the top 2 responses in the final round. A final percentage agreement of 50% or higher was chosen to denote a consensus. Results: In the ambulatory group 60% of caregivers were concerned that their children walked on their toes, 40% agreed that more physio therapy in the community, 45 % concurred that they had difficulty with shoe wear and 35 % agreed that their children had difficulty running and playing sport. The results of the non-ambulatory group were more varied. 20% of parents concurred to have difficulty when trying to open their child's legs to bathe or clean them. 20% agreed that their children were treated differently to other children. 20 % of the parents felt that caring their child became difficult as they got heavier was a major issue they faced and 20 % agreed that their child's muscles being tight was a priority that needed to be addressed. Conclusions: A consensus was reached in the ambulatory group with correction of a child's toe walking being the most frequently reported concern. This should be seen as one of the main treatment priorities when assessing treatment options in an ambulatory child. In the non-ambulatory group, no definitive consensus was reached. This may be due to the fact that children with higher grades of cerebral palsy have many medical complications that have to be addressed and a child's home circumstances and resources may greatly affect what caregivers prioritise as most important to improve the child's quality of life.